A latent profile analysis of self-leadership associated with coping styles among general practice students - Na Zhang; Xiaoyu Ren; Zhen Xu (Scientific Reports)
Abstract General practice students are faced with greater stress and poorer career prospects than other medical students. Self-leadership has an important impact on their coping styles. However, understanding these relationships is complicated by the fact that six types of self-leadership strategies can be combined in various ways based on their levels and shapes. Latent profile analysis, a person-centered method, has helped in addressing these complexities. This study aimed to explore the different profiles of self-leadership among general practice students and differences between different self-leadership profiles and coping styles. A total of 336 general practice students from China were investigated via a self-leadership scale and coping styles scale. Mplus 8.0 was used for latent profile analysis, and BCH was used for subsequent analysis. We identified four profiles of self-leadership: low, medium, medium-high and high. We also found that these self-leadership profiles differentially predicted general practice students’ coping styles. Our findings offer a theoretical basis for targeted interventions aimed at enhancing self-leadership in general practice students, thereby reducing stress and improving coping mechanisms.